Enzymatically stable analogue of the gut‐derived peptide xenin on beta‐cell transdifferentiation in high fat fed and insulin‐deficient Ins1Cre/+;Rosa26‐eYFP mice. Issue 3 (18th August 2020) - Tanday, Neil; Moffett, R. Charlotte; Gault, Victor A.; Flatt, Peter R.; Irwin, Nigel
Abstract: Background: The antidiabetic effects of the gut hormone xenin include augmenting insulin secretion and positively affecting pancreatic islet architecture. Methods: The current study has further probed pancreatic effects through sub‐chronic administration of the long‐acting xenin analogue, xenin‐25[Lys 13 PAL], in both high fat fed (HFF) and streptozotocin (STZ)‐induced insulin‐deficient Ins1 Cre/+ ; Rosa26‐eYFP transgenic mice. Parallel effects on metabolic control and pancreatic islet morphology, including islet beta‐cell lineage tracing were also assessed. Results: Xenin‐25[Lys 13 PAL] treatment reversed body weight loss induced by STZ, increased plasma insulin and decreased blood glucose levels. There were less obvious effects on these parameters in HFF mice, but all xenin‐25[Lys 13 PAL] treated mice exhibited decreased pancreatic alpha‐cell areas and circulating glucagon. Xenin‐25[Lys 13 PAL] treatment fully, or partially, returned overall islet and beta‐cell areas in STZ‐ and HFF mice to those of lean control animals, respectively, and was consistently associated with decreased beta‐cell apoptosis. Interestingly, xenin‐25[Lys 13 PAL] also increased beta‐cell proliferation and decreased alpha‐cell apoptosis in STZ mice, with reduced alpha‐cell growth noted in HFF mice. Lineage tracing studies revealed that xenin‐25[Lys 13 PAL] reduced the number of insulin positive pancreatic islet cells that lost their beta‐cell identity, in keeping with a decreased transition of insulin positive to glucagon positive cells. These beneficial effects on islet cell differentiation were linked to maintained expression of Pdx1 within beta‐cells. Xenin‐25[Lys 13 PAL] treatment was also associated with increased numbers of smaller sized islets in both models. Conclusions: Benefits of xenin‐25[Lys 13 PAL] on diabetes includes positive modulation of islet cell differentiation, in addition to promoting beta‐cell growth and survival.